Biometric Recognition (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
After nearly one year of effort, we are pleased to present this Reprint focusing on cutting-edge advancements in biometric recognition. There are 22 submissions in total, with 11 papers accepted—each peer-reviewed by at least 3 reviewers and accepted based on quality, originality, novelty, and relevance to biometrics. As digital identity integrates into the “Internet of Everything”, this Reprint showcases interdisciplinary innovations spanning sensor design, algorithmic robustness, multi-modal fusion, and real-world applications. The Reprint explores topics including, but not limited to identity-preserving face animation, asymmetric matching of facial representations across heterogeneous models, SAM-iris for accurate iris segmentation, multi-modal ocular segmentation, pioneering VR periocular datasets with emotion annotations, noise-robust periocular and voiceprint authentication, a multi-spectral palm vein system, hybrid network structures for crowd counting, emerging modalities like UWB sensor-based real-time leg movement recognition, and security/ethical discussions. We deeply appreciate the Electronics Editorial Office for hosting this Special Issue and providing professional support, all contributing authors for their rigorous research advancing the frontiers, the peer reviewers for ensuring the scientific quality and novelty of the published works, and the Guest Editors for shaping this interdisciplinary discourse.